2019
DOI: 10.1111/ecc.13043
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the management of cutaneous malignant melanoma. A population‐based high‐resolution study

Abstract: Population‐based cancer registry data from three Spanish areas were used to assess the patterns of care and adherence to guidelines for cutaneous malignant melanoma. We included 934 cases diagnosed in 2009–2013. Completeness of the pathology reports, imaging for detecting distant metastasis and the use of sentinel lymph node biopsy (SLNB) were analysed. The proportion of pathology reports that mentioned the essential pathological features required for T staging was 93%, ranging across geographic areas from 81%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
5
0
1
Order By: Relevance
“…Our results are consistent with those of other studies reporting slightly higher than European mean SLNB frequencies in Spain [ 11 ] and lower ones in Italy [ 29 ]; in both these countries, a remarkable within-country variation in SLNB use was highlighted. In the present study, the large proportion of early-stage melanomas in Spain ( Table 1 ) might explain the overall low odds of SLNB, as well as an RER in line with the European average.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those of other studies reporting slightly higher than European mean SLNB frequencies in Spain [ 11 ] and lower ones in Italy [ 29 ]; in both these countries, a remarkable within-country variation in SLNB use was highlighted. In the present study, the large proportion of early-stage melanomas in Spain ( Table 1 ) might explain the overall low odds of SLNB, as well as an RER in line with the European average.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, SLNB was performed for around 43% of total cases, with notable differences between countries, however, by restricting the analysis to patients with non-metastatic clinically node negative melanoma (cN0M0) with a tumor thickness > 1 mm, for whom the procedure is recommended, the percentage of biopsies rose to almost 70% (69.8%), a figure close to that reported in the US Surveillance Epidemiology and End Results (SEER) in a comparable study period [ 23 ]. Although the intercountry variability in the SLNB use attenuated when considering clinically node-negative cases only, the multivariable analysis confirmed the differences by country, as well as the lower odds of receiving SLNB for elderly than younger patients, a finding reported also by other studies [ 11 , 28 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A previous study found regional differences in survival for various cancers in Spain, most notably for lung cancer [36]. Indications that there is room for improvement have been seen in some high-resolution studies showing geographical variation in the early diagnosis and management of cancer patients in Spain [37,38]. Furthermore, some Spanish studies have reported geographical disparities in infrastructure and equipment for radiation oncology, and in access to oncology drugs and predictive biomarkers [39,40].…”
Section: Discussionmentioning
confidence: 98%
“…In this study 14 CM have been analyzed. They present oval aspects and a fusiform shape, inhomogeneous, hypoechoic, smooth edges, and variable vascularization (1,47,48).…”
Section: Discussionmentioning
confidence: 99%